Comportamento ótico de monocamadas BxCyNz por primeiros príncipios - Oliveira, Fabiano Pereira de (2021)
In recent years, research on two-dimensional (2D) nanomaterials has gradually increased. Among these materials, we highlight those that have similar structural properties, but with different electronic, optical and magnetic properties, such as graphene, a semiconductor of null gap (semimetal) and hexagonal boron nitride (h-BN), an insulator with experimental gap around 5.9 eV. These materials have been the focus of nanotechnology and were studied together as a basis for new nanomaterials with desirable electronic and optical properties. However, for applications in electronics and optoelectronics, such as in the manufacture of semiconductor devices, and in the production of sensors, they must have an gap energy in the range between 1.0-3.3 eV in the visible spectrum. Therefore, an opening energy gap in graphene is extremely important. For this purpose, several theoretical and experimental methods have been developed, one of these is the doping of graphene withh-BN which proved to be effective and, as consequence, hybrid nanostructures with intermediate properties between these two materials were created. In this dissertation we employ a methodology of first principles within the Density Functional Theory (DFT) to study the structural, electronic and optical, twenty BxCyNz monolayers. These monolayers were derived from a graphite layer with insertion of boron, carbon and nitrogen atoms in each location, thus forming two-dimensional structures containing eight atoms arranged in a rectangular lattice and allowing for different stoichiometries. Of the investigated structures, one structure with B3C2N3 stoichiometry to be the most stable. As also in our study it was observed that structures that have the same number of boron atoms and nitrogen showed higher electronic gap values than those that do not have this feature. In the optical properties, we verified that structures of the BC2N − type emit visible light, even in those with indirect gap. Of the analyzed structures, all structures with B2CN stoichiometry behave as metallic (conductive). In relation to electronic properties, we observed that these nanostructures show modulation of energy gap in a range from 0.0 eV (metallic systems) to a maximum value of 2.49 eV (semiconductors). Furthermore, we concluded that nine of the structures studied with BCN2,B2CN2, BC2N and B3C2N3 stoichiometry exhibit optical behavior in the visible spectrum.